Differences in Mental Health among Migrants and Non-migrants in South Africa: Evidence from the National Income Dynamics Study - Govera, Hemish (African Human Mobility Review, 2021)
The literature associates migration with poor mental health outcomes. Despite extensiveempirical research in other countries, there is a paucity of research examining themental health consequences of migration in South Africa, and the factors that compoundthe relationship between the two variables. The study objective was to evaluatethe differences in the mental health status of internal migrants and that of non-migrantsin South Africa with a special focus on depressive symptoms. The study consideredthe influence of various vulnerability and sociodemographic factors such asgender, age, educational attainment, race, income group, marital status and provinceof residence. Mental health disorders are already considered the largest contributor tothe global disease burden. Hence, understanding the nature of the relationship betweenmigration and mental health is critical for public health prevention efforts. To makethe determination, the study applied descriptive analysis and logistic modelling basedon the South African National Income Dynamics Study (NIDS) panel datasets of 2008,2010, 2014/15 and 2017. Descriptive statistics were employed to derive the frequencydistribution of sociodemographic characteristics and migration factors. Logistic regressionanalysis was used to assess the associations between depression, migrationand sociodemographic factors.